Kontribusi Karakter Nuh dalam Noatic Covenant dan Implementasinya Bagi Orang Percaya Masa Kini - Imanoel Seno Nugroho; Verry Willyam; Ketut Mashana Raflesia (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
Through Noah's character God has a new purpose for humanity through the Noahic Covenant. The purpose of this paper is to reflect on the character of Noah, who is considered to have the character of a righteous person in an intimate relationship with God. From his example for believers, we can learn to have a righteous life before God. The method used in this study is a qualitative research of literature by examining the source of the scriptures. The low criticism approach is carried out to describe the meaning contained in it. Through this paper, it is hoped that it can provide an overview of the character and leadership style of Noah as God's people, who were saved from disaster, by a very intimate relationship with God. As well as being a representation of God's plan and love for mankind in eternal salvation.